Analysis of Blood Biochemistry of Free Ranging and Human-Managed Southern White Rhinoceros (Ceratotherium simum simum) Using the i-STAT Alinity v®. (20th July 2021) - Trivedi, Shweta; Burnham, Christina M.; Capobianco, Christian M.; Boshoff, Christiaan; Zheng, Yaxin; Pettiglio, Jordan Wood; Ange-van Heugten, Kimberly; Bissell, Heidi D.; Minter, Larry J.
Abstract : Handheld point-of-care blood analyzers deliver rapid results for biochemical and hematologic parameters, making them very useful in veterinary clinics and in fieldwork applications. This study compared the biochemical and hematologic parameters generated by the novel point-of-care analyzer i-STAT® Alinity V CHEM8+ cartridge between human-managed and free ranging populations of southern white rhinoceros ( Ceratotherium simum simum ). In addition, a novel reference interval for ionized calcium (iCa), a parameter of diagnostic and prognostic importance, was established for southern white rhinoceros. Blood samples were obtained from 10 managed (6 at NC Zoo and 4 at Busch Gardens Tampa Bay in 2019) and 30 free ranging white rhinoceros (collected in South Africa between 2018 and 2019) and analyzed using the i-STAT. Multiple parameters were higher (P < 0.05 ) in free ranging versus managed animals including potassium, blood urea nitrogen, creatinine, glucose, hematocrit, and hemoglobin. Conversely, iCa concentrations were higher (P < 0.05 ) in the managed populations of white rhinoceros. The RI determined for iCa was 1.36–1.56 mmol/L, with a mean of 1.46 mmol/L, and was determined using the guidelines from the American Society for Veterinary Clinical Pathology. There was no difference in anion gap, chlorine, total carbon dioxide, or sodium between the populations. Seasonality and locality of sampling as well as diet may be contributing factors to the higher iCa concentrations in managed rhinoceros. The six elevated parameters in free ranging rhinoceros are likely attributable to dehydration compounded by capture stress. This data provides insight into the state of several biochemical and hematologic parameters in southern white rhinoceros and will allow veterinarians to better assess the health of both managed and free ranging populations.